The determination of the optical constants of Cu(II) compound having 1-chloro-2,3-o-cyclohexylidinepropane thin film - Yakuphanoğlu, Fahrettin; Sekerci, M; Ozturk, OF (Elsevier, 2004)
This paper reports the optical properties of Cu(II) compound having 1-chloro-2,3-o-cyclohexylidinepropane thin film to determine optical constants (refractive index n, extinction coefficient k and dielectric constant e). The optical constants were calculated by using an optical characterization method. The optical band gap and Urbach parameter were determined from the optical spectra. The studies on the thin film revealed that the nature of electronic transition from valence band to conduction band was a direct transition. The exponential behavior of the absorption edge is attributed to the electronic transition in the localized states tailed off in the energy band gap. The spectral dependences of the optical constants show that both the refractive index and extinction coefficient are decreased with wavelength. The real and imaginary parts of the optical conductivity of the thin film were investigated and it is observed that the optical conductivity increases with frequency. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: metal complex; optical constants; optical band gap